The Mechanism of Expansion and the Volatility it created in Three Pheromone Gene Clusters in the Mouse (Mus musculus) Genome - Karn, Robert C. (Oxford University Press, 2009)
Three families of proteinaceous pheromones have been described in the house mouse: androgen-binding proteins (ABPs), exocrine gland–secreting peptides (ESPs), and major urinary proteins (MUPs), each of which is thought to communicate different information. All three are encoded by large gene clusters in different regions of the mouse genome, clusters that have expanded dramatically during mouse evolutionary history. We report copy number variation among the most recently duplicated Abp genes, which suggests substantial volatility in this gene region. It appears that groups of these genes behave as low copy repeats (LCRs), duplicating as relatively large blocks of genes by nonallelic homologous recombination. An analysis of gene conversion suggested that it did not contribute to the very low or absent divergence among the paralogs duplicated in this way. We evaluated the ESP and MUP gene regions for signs of the LCR pattern but could find no compelling evidence for duplication of gene blocks of any significant size. Assessment of the entire Abp gene region with the Mouse Paralogy Browser supported the conclusion that substantial volatility has occurred there. This was especially evident when comparing strains with all or part of the Mus musculus musculus or Mus musculus castaneus Abp region. No particularly remarkable volatility was observed in the other two gene families, and we discuss the significance of this in light of the various roles proposed for the three families of mouse proteinaceous pheromones.